2022
DOI: 10.1186/s12879-022-07352-z
|View full text |Cite
|
Sign up to set email alerts
|

Low CD4/CD8 ratio is associated with increased morbidity and mortality in late and non-late presenters: results from a multicentre cohort study, 2004–2018

Abstract: Background To study whether the association between the CD4/CD8 ratio variation over time and the development of clinical outcomes vary in late presenters (CD4 count < 350/µL or AIDS event at enrolment) or advanced presenters (CD4 count < 200/µL or AIDS event at enrolment). Methods We included ART-naïve adults from the Cohort of the Spanish HIV/AIDS Research Network (CoRIS) enrolled between January 2004 up to November 2018 and with at least 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(13 citation statements)
references
References 29 publications
0
13
0
Order By: Relevance
“…A detailed description of the data adjustment to these cut-offs is included in Supplementary 3 . Six studies ( 28 33 ) were excluded from the meta-analysis due to deviations from our study protocol but were accounted for in the systematic review based on follow-up after ART initiation and reported outcomes. Reasons for exclusion are reported in Supplementary 4 .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…A detailed description of the data adjustment to these cut-offs is included in Supplementary 3 . Six studies ( 28 33 ) were excluded from the meta-analysis due to deviations from our study protocol but were accounted for in the systematic review based on follow-up after ART initiation and reported outcomes. Reasons for exclusion are reported in Supplementary 4 .…”
Section: Methodsmentioning
confidence: 99%
“…Items assessing study attrition showed the highest risk of bias. The overall risk of bias in the included studies was high (n=7; 35%) ( 28 , 30 , 31 , 36 , 37 , 40 , 43 ), moderate (n=11: 55%) ( 9 , 18 , 19 , 21 , 29 , 32 , 33 , 35 , 38 , 39 , 41 ), or low (n=2; 10%) ( 20 , 42 ). Nearly all included studies (n=18; 90%) ( 9 , 18 , 19 , 21 , 28 33 , 35 41 , 43 ) lacked a description of the lost and censored participants, their characteristics, and the methodology for statistical imputation of the missing values.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition to the different CD4/CD8 ratios and CD8 counts used in previous literature to define associations with SNAEs risk, another important source of heterogeneity across studies is the timing of CD4 and CD8 measurements relative to ART initiation, including time-varying variables [11,12,15,27,28] These variables are less interpretable and more challenging to translate to the clinic [29]. Furthermore, measurements taken proximal to the event can make the role of the CD4/CD8 as a predictor less clear [13,25,30].…”
Section: Discussionmentioning
confidence: 99%